HIV Patients Drop Out in Indonesia: Associated Factors and Potential Productivity Loss - Adiatma YM. Siregar; Pipit Pitriyan; Rudi Wisaksana (Acta Medica Indonesiana)
Aim: this study reported various factors associated with a higher probability of HIV patients drop out, and potential productivity loss due to HIV patients drop out. Methods: we analyzed data of 658 HIV patients from a database in a main referral hospital in Bandung city, West Java, Indonesia from 2007 to 2013. First, we utilized probit regression analysis and included, among others, the following variables: patients’ status (active or drop out), CD4 cell count, TB and opportunistic infection (OI), work status, sex, history of injecting drugs, and support from family and peers. Second, we used the drop out data from our database and CD 4 cell count decline rate from another study to estimate the productivity loss due to HIV patients drop out. Results: lower CD4 cell count was associated with a higher probability of drop out. Support from family/peers, living with family, and diagnosed with TB were associated with lower probability of drop out. The productivity loss at national level due to treatment drop out (consequently, due to CD4 cell count decline) can reach US$365 million (using average wage). Conclusion: first, as lower CD 4 cell count was associated with higher probability of drop out, we recommend (to optimize) early ARV initiation at a higher CD 4 cell count, involving scaling up HIV service at the community level. Second, family/peer support should be further emphasized to further ensure treatment success. Third, dropping out from ART will result in a relatively large productivity loss.